Chemical and physical modification of corn starch and application in cupuassu and babassu dairy dessert - Natália Tolfo de Souza; Geovanna Lemos Lima; Gabrieli Oliveira-Folador; Gisele Teixeira de Souza Sora; Ladyslene Chrístyns de Paula; Luís Fernando Polesi (The Journal of Engineering and Exact Sciences)
Corn starch is not suitable for products that require refrigerated storage, due to the high syneresis. To overcome this and other limitations, chemical and physical modifications can be used. Considering the application of Amazonian fruits in a dairy dessert as a way of adding value to the products, this work aimed to modify corn starch with chemical and physical treatments, evaluate its physical-chemical characteristics, apply the modified starch in babassu and cupuassu dairy dessert and evaluate their physical-chemical and sensory properties. The starches were chemically modified by hydrogen peroxide and sodium hypochlorite at 1, 2 and 3% and physically by HMT with 15, 20 and 25% of humidity and annealing at 50, 55 and 60 °C. The modification by hydrogen peroxide caused a considerable decrease in the release of water, with syneresis after 7 days of 0%, so this starch was used in the dairy dessert. The syneresis analysis of the desserts confirmed that the hydrogen peroxide modification was capable of considerably reducing the syneresis of dairy products. The tasters did not feel any significant difference between the samples with native and modified starch in the sensory tests. The mixed dairy dessert received good acceptance and purchase intention.